2000
DOI: 10.1034/j.1399-3003.2000.15e09.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral and bronchial provocation tests with aspirin for diagnosis of aspirin-induced asthma

Abstract: In 35 asthmatic patients with acetylsalicylic acid (aspirin; ASA) intolerance (AIA) and 15 asthmatics tolerating ASA well, the authors compared the diagnostic value of the placebo-controlled oral ASA versus inhaled L-lysine (L) ASA challenges.All AIA subjects gave a history of asthmatic attacks following ingestion of ASA and in all of them the intolerance was confirmed by oral challenge test over the past 10 yrs. Doses of ASA increasing in geometric progression were used in oral tests 10±312 mg (cumulative dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 25 publications
2
129
0
7
Order By: Relevance
“…Provocation protocols for AERD use smaller incremental doses given at longer (3-4-hour) intervals over 2 to 4 days. 34 For a typical 25-kg pediatric patient, the classic provocation protocol would call for a schedule of 25 mg, 50 mg, 100 mg, and 200/250 mg at 30-minute intervals. Both patients challenged in this manner developed severe urticaria, angioedema, and concomitant bronchospasm ϳ1 hour after ingestion of the final dose, with no reaction elicited by the previous doses.…”
Section: Discussionmentioning
confidence: 99%
“…Provocation protocols for AERD use smaller incremental doses given at longer (3-4-hour) intervals over 2 to 4 days. 34 For a typical 25-kg pediatric patient, the classic provocation protocol would call for a schedule of 25 mg, 50 mg, 100 mg, and 200/250 mg at 30-minute intervals. Both patients challenged in this manner developed severe urticaria, angioedema, and concomitant bronchospasm ϳ1 hour after ingestion of the final dose, with no reaction elicited by the previous doses.…”
Section: Discussionmentioning
confidence: 99%
“…Key diagnostic tools to diagnose AERD today are still the lysine-aspirin bronchial challenge test (56) or an oral challenge protocol (57). Recent guidelines (56) recommend a bronchial or a nasal challenge and if the results are negative, an oral challenge to confirm the diagnosis.…”
Section: Aspirin-intolerant Asthmamentioning
confidence: 99%
“…38 A placebo-controlled study by Nizankowska et al reported that 75 mg of prednisone daily for 2 days before aspirin challenge did not provide protection against adverse reaction; however, a 10-day pretreatment protocol protected against or decreased severity of bronchospasm. 39 The authors caution that clinicians attempting to establish aspirin sensitivity via challenge tests should be aware of the possibility of false negative results related to corticosteroid treatment.…”
Section: Corticosteroidsmentioning
confidence: 99%